Single-molecule imaging reveals dimerization/oligomerization of CXCR4 on plasma membrane closely related to its function. Issue 1 (December 2017) - Ge, Baosheng; Lao, Jun; Li, Jiqiang; Chen, Yao; Song, Yanzhuo; Huang, Fang
Abstract Dimerization and oligomerization of G-protein coupled receptors (GPCRs) have emerged as important characters during their trans-membrane signal transduction. However, until now the relationship between GPCR dimerization and their trans-membrane signal transduction function is still uncovered. Here, using pertussis toxin (PTX) to decouple the receptor from G protein complex and with single-molecule imaging, we show that in the presence of agonist, cells treated with PTX showed a decrease in the number of dimers and oligomers on the cell surface compared with untreated ones, which suggests that oligomeric status of CXCR4 could be significantly influenced by the decoupling of G protein complex during its signal transduction process. Moreover, with chlorpromazine (CPZ) to inhibit internalization of CXCR4, it was found that after SDF-1α stimulation, cells treated with CPZ showed more dimers and oligomers on the cell surface than untreated ones, which suggest that dimers and oligomers of CXCR4 tend to internalize more easily than monomers. Taken together, our results demonstrate that dimerization and oligomerization of CXCR4 is closely related with its G protein mediated pathway and β-arrestin mediated internalization process, and would play an important role in regulating its signal transduction functions.